Evaluation of turf grasses for various qualitative and quantitative traits under Malwa Plateau of Madhya Pradesh - KUMAR, TARUN; KUMAR, ANUJ; SONI, NITIN; GALLANI, ROSHAN (Journal of Ornamental Horticulture, 2025)
The present investigation entitled "Evaluation of turf grasses for various qualitative and quantitative traits under Malwa Plateau of Madhya Pradesh" was conducted during December 2020 - May 2021 at the Department of Floriculture and Landscape Architecture, K.N.K. College of Horticulture, Mandsaur (M.P.). The experiment was laid out in a Randomized Block Design with three replications and used different genotypes of turf grasses viz. G1 Palma (Cynodon dactylon L.), G2 Local (Cynodon dactylon L.), G3 Panama (Cynodon dactylon L.), G4 Manila (Zoysia matrella L. Merr. Philipp), G5 Tift dwarf 419 (Cynodon dactylon x Cynodon transvaalensis), G6 Maxican grass (Nassella tenuissima) G7 Selection-1 (Cynodon dactylon L.), G8 Tanu variant, G9 Bargusto (Cynodon dactylon L.) G10 Crow foot grass (Dactyloctenium aegyptium), G11 Bahia grass (Paspalum notatum) G12 Centipede grass (Eremochloao phiuroides [Munro] Hack) with 12 different genotypes. The result revealed that genotype Bargusto (Cynodon dactylon L.) recorded the best performance with respect of most of the parameters i.e., the minimum leaf width (mm), minimum canopy height (cm), smallest leaf length (cm), minimum average stolon internodal length (cm), minimum fresh and dry clipping yield (g/m2). Maxican grass (Nassella tenuissima) was recorded maximum root depth. Maximum shoot density was found in Crow foot grass (Dactyloctenium aegyptium) followed by Bahia grass (Paspalum notatum). Lowest average stolon internodal diameter was noticed in Bahia grass (Paspalum notatum). Among the turf grasses, best performed in turf quality noticed in Tift dwarf 419 (Cynodon dactylon x Cynodon transvaalensis) followed by Crow foot grass (Dactyloctenium aegyptium). Maximum leaf chlorophyll content (SPAD Value) was also recorded in Tift dwarf 419 (Cynodon dactylon x Cynodon transvaalensis).